1973
DOI: 10.1002/j.1537-2197.1973.tb10212.x
|View full text |Cite
|
Sign up to set email alerts
|

Ozone‐induced Membrane Permeability Changes

Abstract: The effect of 0.5 ppm ozone for 0.5‐1 hr on plant cell membrane permeability was ascertained. Permeabilities to both water and solutes were estimated by measuring leaf disc weight changes and following tritiated water and 86Rb fluxes. Measurements were made immediately after ozone exposure and 24 hr after exposure. The reflection coefficient, σ, an index of solute permeability, decreased in ozone‐treated primary leaves of pinto bean (Phaseolus vulgaris). The latter indicates an increase in membrane solute perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Studies on ozone damage to plants have implicated the plasma membrane as the site of initial injury (2,3,8); subsequent ionic and pH imbalance within the protoplasts are likely to disrupt normal metabolic processes (6). The mechanisms of ozone damage to tissues at the molecular level have been studied extensively and are well reviewed (1,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on ozone damage to plants have implicated the plasma membrane as the site of initial injury (2,3,8); subsequent ionic and pH imbalance within the protoplasts are likely to disrupt normal metabolic processes (6). The mechanisms of ozone damage to tissues at the molecular level have been studied extensively and are well reviewed (1,11).…”
mentioning
confidence: 99%
“…ATPase activity of the plasma membrane fractions was determined on 1.0-ml volumes of assay medium (30 mm buffer, 3 (9). However, preliminary experiments indicated that when 3 mm DTE was present in the isolation solutions, ozone had no effect on ATPase activity.…”
mentioning
confidence: 99%
“…The culture solution contained 10 mm KCI, 1.0 mM MgSO4, 1.0 mm KH2PO4, 0.5 mM CaCl2, 5.0 mm NaNO3, and 5.0 mm Na-glutamate as well as sucrose, micronutrients, vitamins, and hormones. Cells were filtered and washed three times at 30-min intervals with a wash solution containing 1 mM CaCl2 and 0.1 mM KCl.…”
Section: Cultured Rose Cellsmentioning
confidence: 99%
“…Ion leakage as a stress response has also been shown to be caused by other factors such as herbicides (14), chilling (7), ozone (5), heavy metals (8), and certain plant pathogens (2). However, while most of these stress factors cause a generalized leakage of a variety of solutes, UV at low fluences causes a specific K+ leakage from cultured rose cells (12).…”
mentioning
confidence: 99%
“…Previously, ozone treatment of plant material has been shown to induce changes in the transport kinetics of many substances, including water (9), sugars (21,22), and ions (6,10). Accordingly, the loss of K+ has been shown to be one of the first indications of membrane permeability changes under a variety of stresses (5,17,18,20).…”
mentioning
confidence: 99%